The effect of sprint training on vertical jump height of female youth volleyball players - Fauzi, N. C. M. (International Journal of Human Movement and Sports Sciences, 2021)
The aim of this study was to investigate the effect of the 60-m sprint training program on the vertical jump height of female youth volleyball players. In this quasi-experimental study, a one-group pretest/posttest design was utilized. Participants were 10 female youth volleyball players (aged 12-15) who were registered in a 12-session sprint training program at a junior sports organization in Yogyakarta, Indonesia. The training program was carried out on a 100-m flat track at the Athletic Field, Faculty of Sport Sciences of Yogyakarta State University. The stand and reach method was used to measure the vertical jump height. To compare the pretest and posttest scores, a paired samples t-test was used. The results indicated that there was a significant increase in vertical jump height from pretest to posttest with a high effect size. Thus, it can be concluded that a 4-week sprint training program can effectively increase the vertical jump height of young volleyball players. It is recommended that volleyball coaches and trainers implement a sprint training program as a step towards developing the vertical jump of their young athletes.